Innovation management and new product development - Trott, Paul (Hoboken : Pearson, 2021)
'It is designed to be accessible and readable. The book emphasises the need to view innovation as a management process. We need to recognise that change is at the heart of it. And that change is caused by decisions that people make. The framework in Chapter 1 (Figure 1.9) attempts to capture the iterative nature of the network processes in innovation and represents this in the form of an endless innovation circle with interconnected cycles. This circular concept helps to show how the firm gathers information over time, how it uses technical and societal knowledge, and how it develops an attractive proposition. This is achieved through developing linkages and partnerships with those having the necessary capabilities'--
Revised edition of the author's Innovation management and new product development, 2017.
Includes bibliographical references and index.
Keywords: Technological innovations -- Management; Industrial management; Product management